Insights in Public Health: Building Support for an Evidence-Based Teen Pregnancy and Sexually Transmitted Infection Prevention Program Adapted for Foster Youth - Smith, Tamara (Hawaii J Med Public Health, 2015)
Hawai‘i Youth Services Network (HYSN) was founded in 1980 and is incorporated as a 501(c) (3) organization. HYSN plays a key role in the planning, creation, and funding of local youth services. One of HYSN's focuses is teen pregnancy and sexually transmitted infections (STI) prevention among foster youth. Foster youth are at a greater risk for teen pregnancy and STI due to a variety of complex factors including instability, trauma, and emancipation from the foster care system. This article highlights how HYSN is leveraging both federal and local funding, as well as other resources, in order to implement an evidence-based teen pregnancy and STI prevention program adapted for foster youth.